(untitled) (Journal of the College of Basic Education, 2022)
If reading is one of the windows of knowledge; It is one of the most important educational toolsMan stands on the results of human thought; Writing is - in fact - a pridethe human mind; Rather, it is the greatest thing that the mind has produced. (Fadlallah 2008: 53) and (Madkoor9 265) and (Al-Khafs 0 2014: 196). Writing is the greatest discovery made by man during his long history ©He was able to record his production and heritage. And to take from the past and present what preparesway for subsequent generations. (Al-Jaafrah. 2011: 273). Writing is the memory of the individual and the nation. It is a record of all aspects of his life and is a source of nooverflowing with all knowledge and sciences; And our whole life is linked directly or indirectly